2017
DOI: 10.1007/978-3-319-66095-0_11
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Mechanism of Cell-Penetrating Peptides

Abstract: Cell-penetrating peptides have been extensively used since their discovery for delivering cargoes unable to cross the cell membrane. Among other transported cargoes, they have shown very efficient delivery for oligonucleotides making cell-penetrating peptides a powerful tool for gene therapy. Numerous cell-penetrating peptides have now been discovered offering a wide library of structures and mechanisms of actions. Nevertheless, if it is known that different pathways are available for particles to be taken up,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 46 publications
0
43
0
1
Order By: Relevance
“…6 ). Hereby, energy-dependent pathways are usually suppressed and direct peptide translocation can be observed [ 36 ]. After treating MCF-7 and HeLa cells for 30 min with the peptides at 4 °C, both fusion peptides were distributed within the cytoplasm and also accumulated in the cell nuclei and nucleoli.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). Hereby, energy-dependent pathways are usually suppressed and direct peptide translocation can be observed [ 36 ]. After treating MCF-7 and HeLa cells for 30 min with the peptides at 4 °C, both fusion peptides were distributed within the cytoplasm and also accumulated in the cell nuclei and nucleoli.…”
Section: Resultsmentioning
confidence: 99%
“…Peptide-mediated transport mechanisms across the plasma membrane include uptake through endocytosis or macropinocytosis (right) [21]; active uptake through receptor-mediated endocytosis (bottom) [22]; and pore formation (left) [23]. Some peptides can mediate transcytosis through sequential endocytic uptake, subcellular transport, and exocytosis [24]. Within cells, peptides can facilitate endosomal escape [22] or nuclear targeting [25], leading to increased RNA delivery or gene transfection.…”
Section: Figurementioning
confidence: 99%
“…(b) Endocytic pathways of CPPs through clathrin and caveolin mediated endocytosis, and macropinocytosis (Reproduced from reference [24], with permission from Springer Nature).…”
Section: Figurementioning
confidence: 99%
“…This suggests that lipid raft-mediated endocytosis may not mediate intracellular delivery of Dot1l, although receptor-mediated endocytosis may be slightly involved. Therefore, we found that endocytosis may not be the major pathway involving the translocation of Dot1l peptide, even though the endocytosis pathway can mediate CPP uptake [30].…”
Section: Different Conditions On the Penetrating Property Of Dot1l Pementioning
confidence: 75%
“…As shown in Figure 3A, our results revealed that fluorescence intensity in the 37 • C group was significantly higher than that of the 25 • C group; however, there were no apparent differences when compared with the 4 • C group ( Figure 3B and Supplementary Figure S1D). These data suggest that Dot1l penetration may partially involve temperature-dependent cellular entry pathways, although some references in the field highlighted an energy-independent contribution to CPP uptake [29][30][31]. To further understand the precise mechanism of Dotl1 peptide uptake, selective and specific interventions in endocytosis studies were conducted.…”
Section: Different Conditions On the Penetrating Property Of Dot1l Pementioning
confidence: 99%